2021
DOI: 10.1007/s12600-021-00962-4
|View full text |Cite
|
Sign up to set email alerts
|

Following the pest outbreak: preliminary findings on the landscape effect on Dasineura oleae and its parasitoids in central Italy

Abstract: Dasineura oleae (Angelini, 1831) (Diptera: Cecidomyiidae), the olive leaf gall midge, is a pest of olive crops that was not problematic in Italy until 2016 when a massive infestation of this pest was reported in a small region in central Italy. We identified infested olive orchards using farmers’ reports and quantified the pest infestation level and parasitism rate in each field. We also explored the effect of the landscape on both the pest and parasitoids using the abundance of olive crops and semi-natural ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Indeed, the abundance of Pteromalidae was not statistically different among olive orchards. The study by Picchi et al [9] supports our evidence, having revealed that olive orchards with higher proportions of Erica spp., P. communis, and other plant species associated with alternative hosts of D. oleae parasitoids in the adjacent SNH had greater parasitism rates than olive orchards with a comparable amount of SNH but lacking those plant species.…”
Section: Local and Landscape Features On D Oleae Parasitoids And On T...supporting
confidence: 89%
See 2 more Smart Citations
“…Indeed, the abundance of Pteromalidae was not statistically different among olive orchards. The study by Picchi et al [9] supports our evidence, having revealed that olive orchards with higher proportions of Erica spp., P. communis, and other plant species associated with alternative hosts of D. oleae parasitoids in the adjacent SNH had greater parasitism rates than olive orchards with a comparable amount of SNH but lacking those plant species.…”
Section: Local and Landscape Features On D Oleae Parasitoids And On T...supporting
confidence: 89%
“…In central Italy, D. oleae populations complete a main generation per year, emerging in late March-early April; however, part of the population may complete a second generation in autumn [8]. Among Mediterranean countries, Italy experienced severe outbreaks of this cecidomyiid pest [9], affecting, on average, 50% of the leaves, but a more severe infestation rate has also been recorded, with peaks of 95% of attacked leaves [8]. Regarding crop damage, the physiological alterations caused by D. oleae on O. europaea have been recently studied [10], but no information is available on the effects on olive yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in olive groves in the central parts of Italy, it was reported that the average number of D. oleae gall was 23%, but this number was up to 71% in some orchards. In addition, some these were reported to have no parasites at all, while this rate reached at 43.7% in some others (Picchi et al, 2022). In Greece, it was reported that the infestation rate of D. oleae was between 70% and 90% in the study region, but the level of infestation varied between trees and the rate of contamination decreased inland (Simoglou et al, 2012).…”
Section: Resultsmentioning
confidence: 90%
“…In the study conducted in Palestine, it was stated that P. oleae was the most effective parasitoid of D. oleae, it was found in all olive groves and in orchards at every height in the region, and the parasitism rate reached up to 82.7% (Batta and Doğanlar, 2019). Although there were 2 species of parasitoids belonging to the Pteromalidae and Platygasteridae families of D. oleae in Italy, it was reported that only P. oleae was the speci c parasitoid of the Gall midge, while the others could parasitize all Cecidomyiidae family species (Picchi et al, 2022).…”
Section: Parazitoids Of Dacineura Oleaementioning
confidence: 99%